Institutional environment and FDI in the context of the COVID-19 pandemic – Case of the Republic of Croatia - Buterin, Vesna (Oeconomica Jadertina, 2021)
The COVID-19 virus pandemic caused unprecedented changes in the behaviour of individuals and economic entities, which then led to a slowdown in economic growth in almost all countries and to a real threat of economic crises whose duration and manifestations will depend on the characteristics and performance of individual national economies. The unpredictability and consequent uncertainty of future economic parameters lead to a restraint and reduction of investments, both domestic and foreign, which in turn has the effect of further reducing growth rates. Experience has shown that countries with a higher level of institutional development managed to overcome economic crises faster and more efficiently, while in countries with poor institutions the crises lasted longer and had the characteristics of sustainability. In recent decades, Croatia has been experiencing institutional stagnation, which has reflected an economic lag behind former transition countries in a number of economic areas, including attracting quality foreign direct investment. On the other hand, due to their specificities, times of crisis are suitable for implementing institutional changes and for accelerated institutional development. The author explores the level of institutional development in Croatia and the possibilities of accelerating institutional growth in the context of future attraction of foreign investments and effects on future economic growth.
Keywords: Institutions; GDP growth rates; pandemic COVID-19; FDI; transition countries